Evolution of specialization in a plant‐microbial mutualism is explained by the oscillation theory of speciation. (1st May 2021) - Torres‐Martínez, Lorena; Porter, Stephanie S.; Wendlandt, Camille; Purcell, Jessica; Ortiz‐Barbosa, Gabriel; Rothschild, Jacob; Lampe, Mathew; Warisha, Farsamin; Le, Tram; Weisberg, Alexandra J.; Chang, Jeff H.; Sachs, Joel L.
Abstract: Specialization in mutualisms is thought to be a major driver of diversification, but few studies have explored how novel specialization evolves, or its relation to the evolution of other niche axes. A fundamental question is whether generalist interactions evolve to become more specialized (i.e., oscillation hypothesis) or if partner switches evolve without any change in niche breadth (i.e., musical chairs hypothesis). We examined alternative models for the evolution of specialization by estimating the mutualistic, climatic, and edaphic niche breadths of sister plant species, combining phylogenetic, environmental, and experimental data on Acmispon strigosus and Acmispon wrangelianus genotypes across their overlapping ranges in California. We found that specialization along all three niche axes was asymmetric across species, such that the species with broader climatic and edaphic niches, Acmispon strigosus, was also able to gain benefit from and invest in associating with a broader set of microbial mutualists. Our data are consistent with the oscillation model of specialization, and a parallel narrowing of the edaphic, climatic, and mutualistic dimensions of the host species niche. Our findings provide novel evidence that the evolution of specialization in mutualism is accompanied by specialization in other niche dimensions.